The Pandemic Within : Policy Making for a Better World - Wagenaar, Hendrik (Book collections on Project MUSE., 2021)
This book offers a blend of moral imagination and social-political analysis to overcome the defects COVID-19 has exposed in our political-economic order. It shows how hegemony and complexity prevent societies from envisioning better practices and institutions and presents feasible solutions.